2019
DOI: 10.3390/su11247167
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence with Bears in Romania: A Local Community Perspective

Abstract: In the modern context of the strict protection of large carnivores, the competition for resources between local community dwellers and these animals has become an important challenge for ensuring coexistence—the key for conservation success. To assess the perceptions of this intricate relationship, six local communities from Central Romania, located in areas with high-density brown bear (Ursus arctos L.) population and frequent conflicts, were investigated. A large proportion of the respondents (69%) showed va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 28 publications
(66 reference statements)
0
16
0
Order By: Relevance
“…The statistical model highlighted that after 1990, the most significant HWI driving forces perceived by locals are represented by two types of management practices, namely: (a) the conservation approach, which allows the increase of wildlife effectiveness and it is supported by active management and restrictive hunting legislation, followed by (b) the economic approach, characterised by a disturbing impact on wildlife natural behaviour, poor management practices of forest administration authorities (lack of food supply from forest rangers and illegal hunting) and rapidly increasing tourism generating habitat loss and wildlife habituation induced by artificial feeding. The conservation practices used to explain the increase of HWI were supported by Stăncioiu et al [19], who revealed that conflicts are a negative side effect of wildlife conservation which affects the coexistence between humans and animals. These conflicts could be prevented by controlling wildlife effectively through sustainable hunting.…”
Section: The Perception Of Local Stakeholders Could Help Us Understand the Hwi Phenomenonmentioning
confidence: 99%
See 3 more Smart Citations
“…The statistical model highlighted that after 1990, the most significant HWI driving forces perceived by locals are represented by two types of management practices, namely: (a) the conservation approach, which allows the increase of wildlife effectiveness and it is supported by active management and restrictive hunting legislation, followed by (b) the economic approach, characterised by a disturbing impact on wildlife natural behaviour, poor management practices of forest administration authorities (lack of food supply from forest rangers and illegal hunting) and rapidly increasing tourism generating habitat loss and wildlife habituation induced by artificial feeding. The conservation practices used to explain the increase of HWI were supported by Stăncioiu et al [19], who revealed that conflicts are a negative side effect of wildlife conservation which affects the coexistence between humans and animals. These conflicts could be prevented by controlling wildlife effectively through sustainable hunting.…”
Section: The Perception Of Local Stakeholders Could Help Us Understand the Hwi Phenomenonmentioning
confidence: 99%
“…By comparison to grey wolves, brown bears are bigger and more powerful. They do not always fear or avoid humans and they engage in conflicts much more frequently [19].…”
Section: The Perception Of Local Stakeholders Could Help Us Understand the Hwi Phenomenonmentioning
confidence: 99%
See 2 more Smart Citations
“…In Romania, as well as in the post-Communist countries of Central Europe, based on the transformations in forest environments and their transition zones with agricultural and urban built-up areas, brown bear conflicts have been increasingly frequent [41,42]. In this context, studies have been carried out on brown bear behaviour and land use in the south-eastern Carpathians of Romania [39]; risk assessments in inhabited areas [43]; brown bear activity in traditional forest pastures in southern Transylvania [43]; biologically realistic annual growth rates; the integration of surveys and telemetry in estimating brown bear density in the Romanian Carpathians [44] and coexistence with brown bears [45] or landscape changes inducing human-wildlife interactions [41]; the use of social networks to develop a better understanding of human-wildlife interactions involving the brown bear in the Prahova Valley-Bucegi Mountains, Southern Carpathians [42]; or conservation issues in the Southern Carpathians, Romanian Carpathians [46].…”
Section: Introductionmentioning
confidence: 99%